Exploration of Multidisciplinary Approaches in Managing Spinal Infections (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Spinal infections, including spondylodiscitis, epidural abscesses, and vertebral osteomyelitis, represent a critical challenge in clinical practice due to their complex diagnosis and management. These infections predominantly affect the lumbar and thoracic regions and are often associated with predisposing factors such as diabetes, immunosuppression, and recent spinal surgeries. This study evaluates 150 cases of spinal infections treated with a multidisciplinary approach, emphasizing the role of advanced imaging modalities like MRI, laboratory markers, and microbial cultures in achieving accurate diagnoses. Key findings highlight that a combination of antimicrobial therapy and targeted surgical interventions significantly improves outcomes, particularly when managed collaboratively by infectious disease specialists, radiologists, and spinal surgeons. The study underscores the importance of early diagnosis and personalized treatment strategies to reduce complications and enhance recovery. This research aims to guide future practices by emphasizing the necessity of integrating advanced diagnostics and multidisciplinary care for spinal infections.